Inducing Saudi High-Tech Exports: Role of Public R&D and Foreign Technology - Mohamed, Nashwa; Kamal, Karima (Jordan Journal of Economic Sciences, 2020)
This study investigates the separate role of public R&D and foreign technology channels, presented by FDI and high tech imports, and their complementary roles in inducing high-tech exports. The ARDL approach is used to estimate the relationship in Saudi Arabia during the period (1992-2016). The findings confirm the superiority of public R&D over the considered foreign technology channels in the short run, while in the long run the role of R&D is only evident in the joint effect with FDI and high-tech imports to absorb the foreign technology transferred by these channels. The findings also confirm the significance of high-tech imports in the long run, individually or jointly with R&D, while FDI is only significant when it interacts with public R&D.